2021
DOI: 10.1371/journal.pcbi.1009070
|View full text |Cite
|
Sign up to set email alerts
|

Novelty is not surprise: Human exploratory and adaptive behavior in sequential decision-making

Abstract: Classic reinforcement learning (RL) theories cannot explain human behavior in the absence of external reward or when the environment changes. Here, we employ a deep sequential decision-making paradigm with sparse reward and abrupt environmental changes. To explain the behavior of human participants in these environments, we show that RL theories need to include surprise and novelty, each with a distinct role. While novelty drives exploration before the first encounter of a reward, surprise increases the rate o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 89 publications
(237 reference statements)
0
39
0
Order By: Relevance
“…In a recent study, Xu et al, 2021 showed that the Bayes Factor surprise modulates human reinforcement learning in a volatile multi-step decision-making experiment and correlates with the EEG P300 amplitude at frontal electrodes. They showed that such a correlation is independent of the correlation of the reward prediction error and novelty with the EEG P300 amplitude (Xu et al, 2021). Although these observations support the computation and the use of the Bayes Factor surprise in the brain, the Bayes Factor surprise Most of these previous studies have focused on one measure of surprise and its role and signatures in behavioral and physiological measurements.…”
Section: A Brief Review Of Experimental Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study, Xu et al, 2021 showed that the Bayes Factor surprise modulates human reinforcement learning in a volatile multi-step decision-making experiment and correlates with the EEG P300 amplitude at frontal electrodes. They showed that such a correlation is independent of the correlation of the reward prediction error and novelty with the EEG P300 amplitude (Xu et al, 2021). Although these observations support the computation and the use of the Bayes Factor surprise in the brain, the Bayes Factor surprise Most of these previous studies have focused on one measure of surprise and its role and signatures in behavioral and physiological measurements.…”
Section: A Brief Review Of Experimental Resultsmentioning
confidence: 99%
“…The generative model describes the subjective interpretation of the environment from the point of view of an agent (e.g., a human participant or an animal). Importantly, we assume that the agent takes the possibility into account that the environment may undergo abrupt changes at unknown points in time (similar to Glaze et al, 2015;Heilbron and Meyniel, 2019;Liakoni et al, 2021;Nassar et al, 2010;Xu et al, 2021). Note, however, that we do not assume that the environment has the same dynamics as those assumed by the agent.…”
Section: Subjective World-model: a Unifying Generative Modelmentioning
confidence: 99%
See 3 more Smart Citations